2022
DOI: 10.3389/fnut.2022.894843
|View full text |Cite
|
Sign up to set email alerts
|

Influence of traditional processing and genotypes on the antioxidant and antihyperglycaemic activities of yellow-fleshed cassava

Abstract: Yellow-fleshed cassava root (YFCR) is processed into traditional products that may influence its bioactivities. In this study, the antioxidant and anti-hyperglycaemic activities of three traditional products (lafun, fufu and gari) from five genotypes (IITA-TMS-IBA070337, 182961, 182962, 182986, 183044) of YFCR were evaluated. The YFCR genotypes were grown at the International Institute of Tropical Agriculture (IITA) research field, Ibadan. The bioactive constituents (total carotenoids, total phenolics, tannins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, this trend is changing as recent research has focused on the bioactive constituents and bioactivity of different traditional products, from biofortified (yellow-fleshed) cassava. For example, our recent study demonstrated the bioactive constituents, antioxidant, and antihyperglycaemic activities of different traditional products (fufu, gari, and lafun) from pVAC biofortified cassava (Kareem et al, 2022). Similarly, Ogbonna et al (2018) reported the blood glucose response in humans due to the consumption of gari produced from different varieties of pVAC biofortified cassava.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, this trend is changing as recent research has focused on the bioactive constituents and bioactivity of different traditional products, from biofortified (yellow-fleshed) cassava. For example, our recent study demonstrated the bioactive constituents, antioxidant, and antihyperglycaemic activities of different traditional products (fufu, gari, and lafun) from pVAC biofortified cassava (Kareem et al, 2022). Similarly, Ogbonna et al (2018) reported the blood glucose response in humans due to the consumption of gari produced from different varieties of pVAC biofortified cassava.…”
Section: Introductionmentioning
confidence: 79%
“…Carotenoids profile of elite yellow-fleshed cassava genotypes Among the 18 elite yellow-fleshed cassava genotypes, IITA-TMS-IBA182962 had the highest (p < 0.05) level of total carotenoids. Carotenoids, which are the pigments in yellowfleshed cassava, were reported to have some desirable healthpromoting activities such as antioxidant activities, immune function enhancement, mammary tumor growth suppression, prevention of blindness dueto age-related macular degeneration, and cardiovascular diseases (Chew and Park, 2004;Ahmed et al, 2005;Elemosho et al, 2021;Kareem et al, 2022). The range of β-carotene level, the predominant carotenoid in yellow-fleshed cassava, quantified in this study is higher than the range (1.12-6.53 µg/g) reported by Odoemelam et al (2020) for yellow root cassava.…”
Section: Discussionmentioning
confidence: 99%
“…The bio-yoghurts’ extracts capacity to scavenge DPPH * was evaluated using the method described by Kareem et al ( 64 ). In brief, extract dilution amounting to 1 mL was mixed with 3 mL of DPPH * solution (60 μM) in a test tube.…”
Section: Methodsmentioning
confidence: 99%
“…Alpha-glucosidase inhibitory activity of the bio-yoghurts was assessed using the method documented by Kareem et al ( 64 ), with slight modifications. The experiment used α-glucosidase (EC 3.2.1.20) and para -nitrophenylglucopyranoside (PNPG) as the enzyme and substrate, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Once the crop is developed, there are no recurring costs other than those associated with conventional agriculture (Díaz‐Gómez et al ., 2017). Yellow‐fleshed cassava varieties are a good source of energy and an essential source of vitamin A in developing countries' diets (Kareem et al ., 2023). Until recently, the enhancement of cassava's nutritive value had not been seriously considered in breeding or processing research.…”
Section: Introductionmentioning
confidence: 99%